Risk Factors for Anthracycline-Induced Cardiotoxicity in Breast Cancer Treatment: A Meta-Analysis - Zhang, Meilin; Yang, Hongguang; Xu, Changcun; Jin, Feng; Zheng, Ang (Frontiers in Oncology, 2022)
Background: Anthracyclines play an important role in the treatment of breast cancer (BC) and other malignant tumors. However, accompanied side-effects are non-ignorable. The purpose of this meta-analysis is to determine the risk factors for anthracycline-induced cardiotoxicity (ACT), so as to identify high-risk patients. Methods: The search for literature was conducted in PubMed, The Cochrane Library, Embase and Web of science. Records were selected with inclusion criteria and exclusion criteria. The newcastle-ottawa scale (NOS) was used to assess the quality of literatures, and Review Manager 5.3 software was used for meta-analysis. Results: Thirteen studies met the inclusion criteria. Meta-analysis indicated that risk factors for ACT were use of trastuzumab (odds ratio [OR]: 2.84, 95% confidence interval [CI]: 2.49-3.22, p < 0.00001), cumulative dose of anthracyclines (OR: 1.45, 95%CI: 1.28-1.65, p < 0.00001), hypertension (OR: 2.95, 95%CI: 1.75-4.97, p < 0.0001), diabetes mellitus (DM) (OR: 1.39, 95%CI: 1.20-1.61, p < 0.0001), tumor metastasis (OR: 1.91, 95%CI: 1.17-3.11, p = 0.009) and coronary heart disease (CAD) (OR: 2.17, 95%CI: 1.50-3.15, p < 0.0001). In addition, our analysis revealed that body mass index (BMI) had no effects on ACT (OR: 1.18, 95%CI: 0.98-1.43, p = 0.08). Conclusions: Patients with high risk for ACT were able to be identified by these factors. For such patients, a higher level of monitoring and protection for the cardiac function should be performed by clinicians.